Study on the antineoplastic and toxicological effects of pomegranate (Punica granatum L.) leaf infusion using the K14-HPV16 transgenic mouse model. (April 2023) - Yu, Manyou; Gouvinhas, Irene; Pires, Maria J.; Neuparth, Maria J.; Costa, Rui M. Gil da; Medeiros, Rui; Bastos, Margarida M.S.M.; Vala, Helena; Félix, Luis; Venâncio, Carlos; Barros, Ana I.R.N.A.; Oliveira, Paula A.
Abstract: Punica granatum L. (pomegranate) has been used in functional foods due to its various health benefits. However, the in vivo biological potential of its leaf remains little known. This study has aimed to characterize the antineoplastic and toxicological properties of using pomegranate leaf infusion (PLI) on transgenic mice carrying human papillomavirus (HPV) type 16 oncogenes. Thirty-eight mice were divided into 3 wild-type (WT) and 3 transgenic (HPV) groups, with exposure to 0.5% PLI, 1.0% PLI, and water. The animals' body weight, drink and food consumption were recorded. Internal organs, skin samples and intracardiac blood were collected to evaluate toxicological parameters, neoplastic lesions and oxidative stress. The results indicated that PLI was safe as no mortality, no behavioural disorders and no significant differences in the levels of microhematocrit, serum biochemical markers, internal organ histology, and oxidative stress was found among the WT groups. Histological analysis revealed that HPV animals that consumed PLI exhibited reduced hepatic, renal and cutaneous lesions compared with the HPV control group. Low-dose PLI consumption significantly diminished renal hydronephrosis lesions and relieved dysplasia and carcinoma lesions in the chest skin. Oxidative stress analysis showed that low-dose PLI consumption may have more benefits than high-dose PLI. These results suggest that oral administration of PLI has the potential to alleviate non-neoplastic and neoplastic lesions against HPV16-induced organ and skin injuries, though this requires further scientific research studies. Graphical abstract: Image 1 Highlights: Pomegranate leaf can serve as green functional food due to many healthy potentials. Pomegranate leaf infusion was non-toxic due to no differences among wild-type groups. The infusions with two dosages significantly diminished renal hydronephrosis lesions. The low-dose infusion relieved dysplasia and carcinoma lesions in the chest skins. The infusion may have antitumoral and curative effects against HPV16-induced lesions.